Morphological characteristics of the lip grooves in citizens of the Republic of North Macedonia determined by Cheiloscopy - Poposki Bojan S.; Babić-Jordamović Naida H.; Ivanovski Kiro B.; Pejčić Ana S.; Kokolanski Vlatko B.; Marjanović Damir J.; Atanasovska-Stojanovska Aneta S.; Jakjovski Zlatko M. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2022)
Introduction: Cheiloscopy is defined as the study of the sulci labiorum, known as "lip prints". Aim of the study: The aim of this study was to determine the morphological characteristics of the lip grooves in the three dominant nationalities in the Republic of North Macedonia (Macedonians, Albanians, Roma) and to compare the obtained results with the morphological characteristics of the lip grooves in three other populations from different geographical regions. Material and methods: In this research, we included 150 examinees aged 25-50 years and divided them into three groups: Macedonians (50), Albanians (50) and Roma (50). The lip prints were taken using microscopic slides and detected using the dactyloscopic powder and brush method. We used the Suzuki and Tsuchihashi classification to typify the lip prints. Results: The most common type of lip grooves in the population of the Republic of North Macedonia was the type II grooves. There was no significant difference in the presence of different types of lip grooves in the four quadrants between males and females, nor between Macedonians, Albanians and Roma. The comparative analysis showed that populations from different geographical areas had different anthropological and morphological characteristics of the lip grooves. Conclusion: Type II lip grooves are the most common in the population of the Republic of North Macedonia and there is no statistically significant difference between the prevalence of different types of lip grooves in the three nationalities in this study. Considering the large number of factors that can affect the quality of the lip print, we recommend that a swab should always be taken before collecting the lip print in order to attempt to extract DNA material from the found trace.